PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DIVISI SUMBER DAYA MANUSIA PADA PT BHUMYAMCA SEKAWAN JAKARTA SELATAN - NIKEN HERAWATI; ASRAH TANDIRERUNG RANTEALLO; KARINA SYAFIRA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Compensation able to improve disicipline and performance an employee for work harder. Employee will achieve their performance if they feel satisfaction with their work. The research was conducted to know the influence of compensation through employee performance at PT Bhumyamca Sekawan Jakarta Selatan. The sample used is saturated sample. The author distributed questionnaires to 35 respondents, then the author process the data using software SPSS version 20. Calculation of the correlation coefficient test obtained a value of 0,965 means that the level of a very strong relationship between compensation for employees performance. The calculation of the coefficient of determination test shows that the value of 93% and 7% influenced by other factors. From the regression equation obtained performance level of 2.625 means that if the effect of compensation is 0 then the level of employees performance is 2.625. It is estimated that the performance value 0,941, meaning that if the value of compensation rises by 1 digit or every increase in compensation by 1% will increase employees performance by 0,941.